The Effect of Daily Timing Variation on some Motor Abilities and Anaerobic Ability among Sabers - Fadhil, Abedulkareem (Journal of Physical Education, 2019)
The idea behind the study is to identify the variation in timing because of its importance in the training work to reach a high level of achievement. A survey style is used to identify the most important variables in the sport of fencing such as motor accuracy, reaction speed, agility, and anaerobic ability.  Each of these variables has been exposed and explained. And in light of the results in chapter four, the researcher came out with several conclusions and addressed recommendations to serve the area of ​​work in the sport of fencing:-• There are significant differences in agility test at 1:00 p.m. (dorsal time) versus the two timings at 10:00 am (in the morning) and 4:00 p.m. (evening).• No significant differences appear among the three timings in reaction speed and anaerobic ability tests for sabers.• In light of these conclusions, recommendations were set including:• To focus on agility within dorsal time taking into account the possibility of developing this ability in the other two timings during the morning and the evening as well.